Pengaruh model kooperatif tipe make a match terhadap kemampuan pemecahan masalah matematis dan motivasi belajar siswa pada kelas III SDN 066652 Bakti Luhur - Taruli Marito Silalahi; Barita Esman Dabukke; Winda Marien Sihite (Journal of Didactic Mathematics, 2022)
The purpose of this research is to determine the effectiveness of cooperative learning model of make a match and to determine whether there are differences on students' motivation and mathematical problem-solvingabilities on multiplication of integers, between learning using cooperative learning model of make a match and conventional. This study is experimental research. The research was carried out at third grade students of SDN 066652 Bakti Luhur. The population was 41 students. The sampling technique used saturated sample; all populations were involved to be used as research samples. The data collection techniques used questionnaires, tests, observation sheets, and documentation. The data analysis technique used analysis prerequisite test, including normality and homogeneity test of the data, N-Gain test and final analysis using t- test. The results showed that learning motivation index value of experimental class was 87.8 including high category, the control class was 73.67 including medium category. The average score of mathematical problem-solving ability in experimental class was 43.80, including high category, while the control class was 24.8 including good category. The results of hypothesis test of differences in learning motivation show that t count > t table with sig. p-value = 11.310 > 0.05), and the difference in mathematical problem-solving ability shows that t count > t table with sig 37.504 > 0.05. So, it can be concluded that cooperative learning model of make a match is effective on students' motivation and mathematical problem-solving abilities.